Bronchoscopic treatment options for chronic obstructive pulmonary disease - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
Chronic obstructive pulmonary disease (COPD) is a major cause of high mortality and morbidity worldwide. Symptoms of the disease are usually related with the results of pulmonary dynamic hyperinflation. Treatment options are classified as invasive-noninvasive and mostly tend to be palliative. Lung volume reduction techniques are invasive part of the treatment and can be performed by surgical or bronchoscophic methods. Because of the low complication rates bronchoscophic methods became more popular in recent years. Patients presenting with severe air trapping and thoracic hyperinflation have the greatest potential to derive benefit from volume reduction procedures. Assessment of patients should ideally include cardiological evaluation, high resolution CT scan, ventilation and perfusion scintigraphy, full pulmonary function tests, and cardiopulmonary exercise testing. There are three main groups of bronchoscophic volume reduction, direct effect on lung parenchyma, airway bypass and blocking the airways. Indications and contraindications are different for each modality and device. Patients who have deterioration despite habitual changes and medical therapies should be evaluated for volume reduction procedures.
Keywords: COPD; Emphysema; Hyperinflation; Lung volume reduction; Bronchoscopic